Vemurafenib treatment for patients with locally advanced, unresectable stage IIIC or metastatic melanoma and activating exon 15 BRAF mutations other than V600E. Issue 6 (December 2017) - Hallmeyer, Sigrun; Gonzalez, Rene; Lawson, David H.; Cranmer, Lee D.; Linette, Gerald P.; Puzanov, Igor; Taback, Bret; Cowey, C. Lance; Ribas, Antoni; Daniels, Gregory A.; Moore, Timothy; Gibney, Geoffrey T.; et al.
Abstract : BRAF mutations are found in ~50% of metastatic melanomas, most commonly in codon V600. Vemurafenib improves progression-free survival and overall survival in patients with advanced BRAF V600E -mutated melanoma. The results of a descriptive study evaluating vemurafenib in patients with advanced melanoma harbouring BRAF mutations other than V600E are reported. Eligible patients with stage IIIC or IV melanoma and non-V600E BRAF mutations received vemurafenib (960 mg, twice daily). End points included investigator-assessed best overall response rate (primary), time to response, duration of response, progression-free survival, overall survival and safety. Planned (V600K vs. non-V600K mutations) subgroup analyses were carried out. Thirty-one patients were enrolled; 13 (42%) had V600K mutations and 18 (58%) had other mutations. Investigator-assessed confirmed that the best overall response rate was 23% (95% confidence interval=10–41%) in the overall population, and was similar between patients with V600K mutations (23%; 95% confidence interval=5–54%) versus other mutations (22%; 95% confidence interval=6–48%). Responses were observed in patients with V600K ( n =3), V600E2 ( n =1), V600R ( n =1), L597S ( n =1) and D594G ( n =1) mutations. No new safety signals were reported. Vemurafenib showed activity in patients with advanced melanoma with rarer BRAF mutations. Abstract : Supplemental Digital Content is available in the text.